# emitter n collecter current........

Discussion in 'General Electronics Chat' started by ashutosh tiwari, Apr 7, 2010.

1. ### ashutosh tiwari Thread Starter New Member

Mar 19, 2010
8
0
i wanna bjt we som time assume collecter current equal to the emittr n why some time not.......

2. ### Engr Member

Mar 17, 2010
114
5
In terms of Ic you have this formula: Ic = Ib * B
where B = beta and Ib = base current.
In terms of Ie you have this formula: Ie = Ib + Ic
where Ic = collector current and Ie = emitter current
If the 1st equation is substituted to the 2nd equation in terms of Ic you will have this equation Ie = (Ic/B) + Ic

Extracting Ic you will have this equation Ie = Ic((1/B) + 1)

Typically B = 100 so ((1/B) + 1) is approximately equal to 1

With this Ie is also approximately equal to Ic.

Hope this helps.....

3. ### kkazem Active Member

Jul 23, 2009
160
28
Hi all,
I just wanted to say to Engr, excellent analysis, your spot-on.

Regards,
Kamran Kazem

ashutosh tiwari likes this.
4. ### ashutosh tiwari Thread Starter New Member

Mar 19, 2010
8
0
thanks alot.......................